(untitled) (Bangladesh Medical Journal Khulna, 2012)
It was a prospective study carried out of all cases of haematemesis and or melaena at Rajshahi Medical College Hospital between December 2004 and March 2005 and determined demographic profile, clinical presentation, cause and outcome of upper gastrointestinal bleeding in a tertiary hospital of Bangladesh. Fifty adult patients presenting with haematemesis and or melaena admitted consecutively into medical units were evaluated through proper history taking, thorough clinical examination, endoscopic examination within 48 hours of first presentation and other related investigations. Patients who were not stabilized haemodynamically within 48 hours of resuscitation and endoscopy could not be done within that period were excluded from this study. Out of 50 patients 44 were male and 6 were female and average age of the patients was 39.9 years. Most of the patients belonged to low socio-economic condition- Farmers (22%), Service holder (18%), Laborers (l6%), Students (l4%), Businessman (8%), House wife (4%) and others (l8%). Farmers, service holders and laborers were the most affected group (57%). Among the patients monthly income (Tk) was > 20000/= (2%), 15000-20000/= (8%), 8000-15000 /= (10%) and 0-8000/= (80%). Haematemesis and melaena (42%), melaena (42%), Haematemesis (16%) were the presenting features. Endoscopy revealed that duodenal ulcer (34%) was the most common cause of upper gastrointestinal (GI) bleeding followed by rupture of portal varices (16%), neoplasm (10%), gastric ulcer (08%) and gastric erosion ( 06%). Peptic ulcer disease still remains as the major cause of upper (GI) haemorrhage though cases of ruptured oesophageal varices are gradually increasing. DOI: http://dx.doi.org/10.3329/bmjk.v43i1-2.13014 Bang Med J (Khulna) 2010; 43: 3-6